Does Publisher Volume Matter? A Cross-Sectional Analysis of Scopus Journal Publishing Patterns - Eungi Kim (Publications)
The objective of this study is to examine the relationship between publisher volume—the number of journals a publisher produces—and journal publishing patterns in Scopus, including various journal metrics such as the h-index, SCImago Journal Rank (SJR), and journal quartiles. The SCImago database, which is derived from Scopus data, serves as a proxy for journal impact and influence. The analysis also considered factors such as Open Access (OA) status, geographical location, and subject areas. Using the 2023 SJR dataset, publishers were classified into four categories: V1 (single journal), V2 (2–9 journals), V3 (10–99 journals), and V4 (100+ journals). The findings showed that V4 publishers accounted for 44.5% of Scopus-indexed journals despite comprising only 0.3% of all publishers, whereas V1 publishers represented 78.6% of all publishers but contributed only 21.3% of journals. High-volume publishers had more journals ranked in Q1 and Q2, while lower-volume publishers were more concentrated in Q3 and Q4. Results from the linear mixed-effects model indicated that publisher volume was associated with journal metrics, with higher-volume publishers generally achieving higher h-index and SJR scores. Western Europe and North America had the highest number of V4 publishers, whereas China, Spain, and Italy exhibited strong journal production but had fewer publishers in the highest-volume category. These results illustrate the dominance of a small group of high-volume (V4) publishers and the challenges smaller publishers face in gaining visibility and impact. They also underscore the need to consider policies that foster a more balanced and equitable scholarly publishing environment, particularly for underrepresented regions and subject areas.